Technical Resilience in Intrapreneurs for Product Innovations : An Exploratory Study - Sehgal, Anuja; Saxena, Neelam; Pradhan, Sajeet (Prabandhan: Indian Journal of Management, 2022)
Technical resilience in intrapreneurs was accepting realities and taking responsible actions through leading change. This research paper actualized an exploratory analysis of technical resilience leadership of intrapreneurs working in hi-tech product innovation companies. It deliberated on technical resilience leadership patterns of technical engineers and their socio-conscious progressive behavior in a technically competitive world. The paper conducted a descriptive, compared means, and exploratory analysis of the technical resilience leadership of 240 intrapreneurs and their product innovations with a statistical tool (SPSS). It examined intrapreneurs’ visionary thinking, opportunity-seeking, capability-building, and environment-conscious behavior for creating novel product innovations. It evaluated the different scenario plans and featured the innovative work behaviors of intrapreneurs through novel product innovations. Scenarios significantly built high-risk-taking capabilities to address future uncertainties/complexities and improve social well-being. The exploratory analysis explored the core determinants of technical resilience leadership and their effect on assessing the usefulness of scenario plans for novel productions. The paper expressed the importance of scenario planning for change-making and building something new for societal value. The article meaningfully called the attention of audience readers, practitioners, scenario definers, policy formulators, academicians, and technopreneurs (intrapreneurs) on sense-making and differential approaches to scenario planning and idea building for fruitful, innovative production outcomes via technical resilience leadership. The paper proposed the various aspects of technical resilience leadership in intrapreneurs that concurrently led them to high scenario planning efforts for innovative project ideas with a keenness for resilient, differential action behavior.